Ability of Patients to Distinguish Among Cardiac Genomic Variant Subclassifications. (June 2018) - Hellwig, Lydia D.; Biesecker, Barbara B.; Lewis, Katie L.; Biesecker, Leslie G.; James, Cynthia A.; Klein, William M.P.
Abstract : Background: Clinical genetic testing for heritable cardiovascular disease has become a widely used tool to aid in the management of patients and their families. A 5-category variant classification system is commonly used for genetic test results, but some laboratories further subclassify variants of uncertain significance. How and whether patients perceive differences among the variant categories or subclassifications of variants of uncertain significance is unknown. Methods: We tested whether participants perceived differences in genetic variant subclassifications on outcomes including risk comprehension, risk perception, worry, perceived uncertainty, and intentions. Order-randomized hypothetical cardiovascular genetic results were given to 289 participants enrolled in a genome sequencing study. Three categories of variants were presented to participants: variants of uncertain significance, possibly pathogenic, and likely pathogenic. Responses to the first variant presented were analyzed in a between-groups analysis, and responses to all 3 variants were analyzed in a within-groups analysis. Results: When presented with all 3 results, participants distinguished among the subclassifications on all outcomes ( P <0.001). When given only a possibly pathogenic result, their risk perceptions were similar to those of variants of uncertain significance, but they were more worried and intended to behave as if they had received a likely pathogenic result. Individuals depended more on their affective responses such as worry when they received only one result ( P <0.05). Conclusions: Participants are better able to distinguish pathogenicity subclassifications when presented with multiple categories. Individuals who receive a single uncertain result in a cardiovascular disease gene may benefit from interventions to decrease worry, calibrate risk perceptions, and motivate variant-appropriate behaviors. Abstract : Supplemental Digital Content is available in the text.